THE UTILIZATION OF PET WASTE AS RAW MATERIAL FOR PRODUCING MONOFILAMENT YARN : THE EFFECT OF WINDING SPEED ON THE PHYSICAL AND MECHANICAL PROPERTIES OF THE YARN - Abdurrohman Abdurrohman; Valentinus Galih Vidia Putra; Akbar Hanif Dawam Abdulllah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
THE UTILIZATION OF PET WASTE AS RAW MATERIAL FOR PRODUCING MONOFILAMENT YARN : THE EFFECT OF WINDING SPEED ON THE PHYSICAL AND MECHANICAL PROPERTIES OF THE YARN. Plastic waste production in Indonesia is quite high, reaching 15% to the total national waste production or 189-kilo tons/day with an average growth of 14.7% per year, the second biggest contributor after organic waste. This fact greatly affects human health and the environment since plastic is difficult to degrade, estimated to require 100 to 500 years for the plastic to decompose completely. Therefore, recycling becomes a popular solution to reduce waste or plastic waste by turning it into new products that have added value. Plastic materials, such as PET, have thermoplastic properties which become a special potential to use as recycled materials. The aim of this research was to study the ability of PET plastic waste as a raw material for making monofilament yarn by melt-spinning methods. PET plastic waste is melted at 250-260 °C, then is extruded using a prototype melt-spinning tool with a single spinneret hole which the diameter is 3 mm into a monofilament yarn using three variations of winding speed (a) 43.33 m/min, (b) 59.35 m/min and (c) 72.72 m/min The results showed that the yarn with the highest winding speed (variation C) produced yarn with the highest fineness, reaching (30.06± 4.82) denier, and the best tensile strength compared with the other, reaching (47.7±14,97) MPa with elongation of of (10± 9.65) %.